2003
DOI: 10.1002/ajim.10162
|View full text |Cite
|
Sign up to set email alerts
|

National Health Interview Survey mortality among US farmers and pesticide applicators

Abstract: Compared to all other workers, farmers and pesticide applicators were at greater risk of accidental mortality. These pesticide-exposed workers were not at an increased risk of cancers possibly associated with exposure to estrogen analogue compounds, but were at an increased risk of hematopoietic and nervous system cancers. NHIS mortality follow-up represents an important occupational health surveillance instrument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 32 publications
(38 reference statements)
0
49
0
Order By: Relevance
“…This occurs because both elements compete for binding at the same binding site at metallothionein (Centers for Disease Control and Prevention [CDC], 2006). Exposure can occur in many forms such as through inhalation, ingestion and dermal contact (Dosemeci et al, 2002;Nordin et al, 2001), as well as during handling (Jeyaratnam, 1990), which involve spraying, transporting or delivering, storing, processing and disposing of pesticide and fertilizer (Fleming, Gomez-Martin, Zheng, Ma, & Lee, 2003). In these exposures, the pesticides have been found to be involved in several diseases that can eventually cause death.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs because both elements compete for binding at the same binding site at metallothionein (Centers for Disease Control and Prevention [CDC], 2006). Exposure can occur in many forms such as through inhalation, ingestion and dermal contact (Dosemeci et al, 2002;Nordin et al, 2001), as well as during handling (Jeyaratnam, 1990), which involve spraying, transporting or delivering, storing, processing and disposing of pesticide and fertilizer (Fleming, Gomez-Martin, Zheng, Ma, & Lee, 2003). In these exposures, the pesticides have been found to be involved in several diseases that can eventually cause death.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of these differences are unknown. Two recent cohort studies reported an increased risk for CVD among farmers (RR 1.4, 95% CI 1.2-1.7) in a comparison with all other adult workers in the United States (38) and an increased proportionate mortality ratio for myocardial infarction in farmers (39). However, none of these studies linked the increased risk of CVD with inflammation related to the work environment.…”
Section: Discussionmentioning
confidence: 99%
“…A complete description of NHIS methodology is provided elsewhere [NCHS, 2006[NCHS, , 2012NIOSH, 2012a]. The NHIS has been used as a focused source of health outcome data in a variety of recent industry-and occupation-related studies [Robinson et al, 2011;Dillon et al, 2002;Fleming et al, 2003;Kriebel et al, 2004;Gomez-Marin et al, 2005;Yassin, 2007;Tak and Calvert, 2008;Bang et al, 2009;Forrest and Cali, 2009;Vidal et al, 2009;Zhang et al, 2009;Lombardi et al, 2010;Luckhaupt et al, 2010;Arheart et al, 2011;Syamlal et al, 2011].…”
Section: National Health Information Survey (Nhis)mentioning
confidence: 99%
“…For example, although our results are suggestive, we cannot prove that the personal choices made by workers in terms of health behaviors and habits (e.g., smoking, weight status, and exercise) are causally linked to reported disease and chronic conditions such as hypertension and heart disease; although given the depth and extent of evidence for causal linkages from over 50 years of scientific investigation it is not likely that the observed associations are totally confounded by unidentified risk factors The NHIS does not consistently collect data on occupational exposure as it relates to differing job demands across varying industries, so direct associations with occupational health effects or outcomes cannot be made. The self-report nature of the NHIS survey and potential problems with the respondent's interpretation and understanding of how questions are asked or worded may contribute to under-and overreporting biases [Fleming et al, 2003]. For example, research suggests that people tend to under-report their weight and over-report their height leading to an underestimation of BMI [NIOSH, 2012a].…”
Section: Strengths and Limitationsmentioning
confidence: 99%